2020
DOI: 10.1039/d0ra04780e
|View full text |Cite
|
Sign up to set email alerts
|

Targeting G-quadruplex DNA with synthetic dendritic peptide: modulation of the proliferation of human cancer cells

Abstract: A synthetic dendritic peptide, targeting human telomeric G4 DNA, inhibits the telomerase and lessens the proliferation of human cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…However, a loop-binding mode and groove interactions were proposed for the peptide-hemicyanine conjugates, without significant π-stacking with the DNA bases. [64] By employing a series of analytic techniques, including gel mobility shift assay, isothermal titration calorimetry, fluorescence spectroscopy and DNA-thermal denaturation experiments followed by ECD, Biswas et al [65] showed that a synthetic dendritic peptide, Cd2-(YEE)-E (Figure 6), specifically targets h-Telo G4. Interestingly, the same dendritic peptide inhibits the growth of HeLa and U2OS human cancer cells lines, inducing apoptosis in vitro.…”
Section: Artificially and Naturally Derived Peptides Interacting Spec...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, a loop-binding mode and groove interactions were proposed for the peptide-hemicyanine conjugates, without significant π-stacking with the DNA bases. [64] By employing a series of analytic techniques, including gel mobility shift assay, isothermal titration calorimetry, fluorescence spectroscopy and DNA-thermal denaturation experiments followed by ECD, Biswas et al [65] showed that a synthetic dendritic peptide, Cd2-(YEE)-E (Figure 6), specifically targets h-Telo G4. Interestingly, the same dendritic peptide inhibits the growth of HeLa and U2OS human cancer cells lines, inducing apoptosis in vitro.…”
Section: Artificially and Naturally Derived Peptides Interacting Spec...mentioning
confidence: 99%
“…These experiments led to the conclusion that this peptide, upon targeting the telomeric G4 DNA, is an inhibitor of tumor cell growth by inducing apoptosis. [65] In order to improve the selectivity and specificity of the peptide ligands for h-Telo G4, Tyagi et al designed the QW10 peptide, with sequence QQWQQQQWQQ. QW10 was chosen to incorporate glutamine amino acid for its capacity as hydrogen bond donor and acceptor with guanine, and tryptophan to provide π-stacking with the quartet in an intercalative mode.…”
Section: Artificially and Naturally Derived Peptides Interacting Spec...mentioning
confidence: 99%
See 1 more Smart Citation
“…Systems capable of controlling DNA and RNA G-quadruplex structures would be useful for the modulation of various cellular events and different G-quadruplex-targeting ligands have been described [ 17 , 18 ], including phthalocyanine [ 19 ], porphyrin [ 20 ], and other derivatives [ 21 , 22 ]. From these, peptides represent a class of highly specific ligands with a greater degree of functionality including binding on-off switching, cellular penetration, and the ability to target organelles [ 23 , 24 , 25 , 26 , 27 ]. Among them, the N-terminal domain of the RNA helicase associated with AU-rich element (RHAU), a member of the human DEAH (Asp-Glu-Ala-His) box family of RNA helicases, which includes a specific motif, named RSM, necessary for G-quadruplex recognition and interaction (aa 54–66) [ 28 ], has recently raised the interest of several authors [ 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported a selective recognition of human telomeric G4 DNA by engineered peptides, which exhibit high content of glutamic acid and tryptophan residues [147]. Furthermore, it has been shown that synthetic dendritic peptide, C-(YEE)-E could stabilized human telomeric G4 DNA structure and also has the potential to inhibit the proliferation of human cancer cells in vitro [148].…”
Section: Alternative G4-binding Ligandsmentioning
confidence: 99%